Mouse in vivo-derived late 2-cell embryos have higher developmental competence after high osmolality vitrification and −80°C preservation than IVF or ICSI embryos - Erika HAYASHI; Sayaka WAKAYAMA; Daiyu ITO; Ayumi HASEGAWA; Keiji MOCHIDA; Masatoshi OOGA; Atsuo OGURA; Teruhiko WAKAYAMA (The Society for Reproduction and Development, 2022)
Mammalian embryos are most commonly cryopreserved in liquid nitrogen; however, liquid nitrogen is not available in special environments, such as the International Space Station (ISS), and vitrified embryos must be stored at −80°C. Recently, the high osmolarity vitrification (HOV) method was developed to cryopreserve mouse 2-cell stage embryos at −80°C; however, the appropriate embryo is currently unknown. In this study, we compared the vitrification resistance of in vivo-derived, in vitro fertilization (IVF)-derived, and intracytoplasmic sperm injection (ICSI)-derived mouse 2-cell embryos against cryopreservation at −80°C. The ICSI embryos had lower survival rates after warming and significantly lower developmental rates than the in vivo and IVF embryos. Further, IVF embryos had a lower survival rate after warming, but a similar rate to the in vivo embryos to full-term development. This result was confirmed by simultaneous vitrification of in vivo and IVF embryos in the same cryotube using identifiable green fluorescent protein-expressing embryos. We also evaluated the collection timing of the in vivo embryos from the oviduct and found that late 2-cell embryos had higher survival and developmental rates to full-term than early 2-cell embryos. Some early 2-cell embryos remained in the S-phase, whereas most late 2-cell embryos were in the G2-phase, which may have affected the tolerance to embryo vitrification. In conclusion, when embryos must be cryopreserved under restricted conditions, such as the ISS, in vivo fertilized embryos collected at the late 2-cell stage without long culture should be employed.